Impact of Underground Space Height and BMI on Children’s Fatigue During Ascending Evacuation: An Experimental Study and Intelligent Assistive Implications - Ming Liu; Hu Zhang; Xin Guo; Yongbo Feng; Xiaochen Zhao; Changzheng Xuan; Xiaohu Jia (Buildings, 2025)
With the rapid expansion of urban underground spaces, safety concerns related to ascending evacuation have become increasingly critical, particularly for children, who are more susceptible to fatigue than adults. However, most existing research focuses on adults and overlooks the unique needs of children. This study investigated two key fatigue-related factors, evacuation height and body mass index (BMI), to construct a predictive model of children’s fatigue levels and proposed a non-invasive, code-compliant assistive solution integrated into underground fire escape stairways. Data were collected from 41 child participants during an ascending evacuation under simulated emergency conditions using real-time heart rate monitoring and video analysis. Statistical correlation and regression modeling revealed a significant positive correlation between evacuation height and heart rate (p < 0.01). Female participants exhibited higher mean heart rates and greater variability, with a strong positive correlation between BMI and heart rate observed in females (p < 0.01). Regression analysis showed that heart rate increased with BMI but plateaued in the obese group. These findings demonstrate that evacuation height and BMI significantly influence children’s fatigue levels. Based on these physiological insights, this study proposes a non-invasive architectural intervention to enhance children’s evacuation performance, offering practical guidance for the design of intelligent evacuation systems. Furthermore, it provides theoretical support for child-centered assistive design and safety improvement within the boundaries of current fire protection codes.